TINGKAT MOTIVASI DALAM MENGIKUTI EKSTRAKURIKULER BELA DIRI KARATE (Studi Survei Peserta Didik di SMP Negeri 2 Kembayan) - Sirapika Sirapika; Victor G Simanjuntak; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this study is about the ups and downs of students' motivation in participating in Karate extracurricular activities at SMP N 2 Kembayan. The purpose of this study is to determine the level of student motivation in participating in Karate extracurricular at SMP N 2 Kembayan. The research method used in this research is descriptive quantitative. The sample used the saturated sample technique, that is all 20 students of SMP N 2 Kembayan who took Karate extracurricular activities. The data collection technique used in the study is questionnaire, which is measured using a Likert scale. Data analysis was carried out to find the percentage by dividing the actual score by the ideal score multiplied by 100%. The results of the reliability test calculation show that the Cronbach alpha value > r count (0,656 > 0.632). The results of the research, and data analysis showed that the average of the results of the intrinsic factor was 36.6%, while the result of the extrinsic factor was 63.4%. Thus, it can be concluded that the most dominant factor in students' motivation towards karate extracurricular is external factors with 63.4%.Keywords: Motivation, Extracurricular, beladiri